Patient Satisfaction in Baharloo Hospital in 2008 - N Talaei; M Arefi (Tehran University of Medical Sciences, 2010)
Background and Aim: Given The importance of patient satisfaction levels of health care is an effective role in planning health services management system. This study aimed to assess patient satisfaction of hospital services and related factors was designed in Baharloo study Hospital.Materials and Methods: This is a cross sectional. The data is collected by questionnaire and interview and after completing the questionnaire based on the number of samples required in this study, the information was collected into the computer and analyzed.The study statistical society was 320 patients hospitalized in all different parts of the hospital in the second six months of 1387 were selected in the form of the random sampling . To measure the patient satisfaction used satisfaction questionnaire with six demographic questions and 20 satisfaction terms. Questionnaires was given to the patients by trained persons (non-medical staff) in the last session of therapy.In young patients the questionnaire was completed by the patients family or friend and about cases with illiteracy or low literacy the questionaire was completed by Trained questioners.Listen.Results: Satisfaction including satisfaction levels was as follows: heat and cooling systems (44.8%)- facilities (48.3%) - Food Quality (44.8%) - daily clothes and sheets change(41.6%)- Sanitation and hygience (48.3%) - room lighting ( 56%) - the speed of filing reception files(58.6%)- Nurse attitude (55.2) - time presence of clinical nurses on the patient's bedside (58.6%) - appropriate communication with sick relatives (55.2%). Highest level of patient satisfaction was as follows: satisfaction of nurse time presence on the patient's bedside (58.6) - the speed of filing reception files and the patient good guidance by receptionist(58.6%) and room lighting (58%).Discussion and Conclusion: The largest percentage of patient dissatisfaction was regarding facilities of rooms, food quality and daily clothes and sheet change(24.1%).